OPTIMALISASI PENGELOLAAN ASET DAERAH GEDUNG PONTIANAK CONVENTION CENTER PONTIANAK - Nugroho, Yoyok Setyo; Agustiar, Memet; Rosyadi, Rosyadi (Jurnal Ekonomi Daerah (JEDA), 2020)
This study, entitled Optimizing Regional Asset Management in the Pontianak Convention Center Building, aims to analyze the economic optimization of the PCC building by calculating property values and PCC building rental income potential, using survey data with a cost approach and revenue approach, and a lease determination based on Peremdagri No. 19 2016.The analysis shows that the estimated property value of the Pontianak Convention Center building calculated using the cost approach is Rp28,415,461,957.60. Based on the income approach is Rp27,449,227,531.45, so the middle value of Rp27,932,344,744.52 is used, the value of the land used by the building is Rp69,054,757,200.00, so that the property value of the PCC building and building assets is Rp 96,987,101,944.52. Estimated rental value of Pontianak Convention Center building which is calculated based on Permendagri Number 19 of 2016 is Rp18,210,328.14, it’s specified according to the floor, that for a base floor rate is 65% x 18,210,328.14 = Rp 11,836,713.29 and an upper floor is Rp. 6,373,614.85 per day. The results of this assessment are far above the average value prevailing so far, so that the contribution to Pontianak City's PAD (local revenue) is very low, the value of the contribution of PCC building levies is quite large, reaching 42.31% of the total lease fees of Pontianak City.Keywords: Optimization, asset value, rental value